Inequalities and Segregation across the Long-Term Economic Cycle: An Analysis of South and North European Cities - Tiit Tammaru; Szymon Marcińczak; Raivo Aunap; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
The aim of this paper is to get new insight into the complex relationship between social inequalities and socioeconomic segregation by undertaking a comparative study North and South European cities. Our main finding shows that during the last global economic cycle from the 1980s through the 2000s, both levels of social inequalities and socio-economic segregation have grown. However, the effects of rising levels of inequality affect levels of segregation with a strong time lag. This reminds us that the effect of the most recent economic crisis will most likely be long-term, especially in the South of Europe.
Keywords: N94; O18; P25; R21; R23; 330; social inequalities; residential segregation; comparative urban studies; South Europe; North Europe